Impressive Analysis of High School Students' Abilities in Physics Measurement Materials of the New Indonesian-Paradigm Curriculum Via the Rasch Model - Amiruddin, Mohd Zaidi Bin; Samsudin, Achmad; Coştu, Bayram; Suhandi, Andi; Kaniawati, Ida; Apriliyanti, Nila (JIPF (Jurnal Ilmu Pendidikan Fisika), 2024)
The extent of students' abilities is an important thing to consider because it is part of the learning process. This research analyzes students' abilities in the subject matter measurement physics. Tools that are used is a ministep Rasch analysis. Descriptive quantitative was used in the study by providing an overview of the student's results and supported by data in the form of numbers from Rasch analysis. A total of 14 participant students as respondents in this research with the criteria of having received physics and measurement materialize Merdeka Curriculum in his learning. The results of this research state that ability learners are still classified as low, although it has obtained that material, while Cronbach's alpha index (0.62) is in the moderate category. Besides that, suitability questions for students still need to be classified as low. That way, it is important to balance the equations with students' abilities or vice versa. In the future, study continuation is required to increase students' abilities. According to the claim from the Merdeka Curriculum, it is learning more about the essentials.